MENINGKATKAN KEMAMPUAN MENGERJAKAN TES TOEFL (TEST OF ENGLISH AS A FOREIGN LANGUAGE) MELALUI IMPLEMENTASI TEKNIK MIND MAP ( Experimental Research pada Mahasiswa STAIN Jurai Siwo Metro) - Arini, Yusti (P3M STAIN Jurai Siwo Metro, 2012)
This research is aimed at identifying what difficulties the students have in doing the TOEFL (Test of English as a Foreign Language) test; a standardized test to measure a personâs global English competence. To solve the problems, Mind Map technique, a process of mapping the mind to correlate the certain problems from the neuron cells forming the concept correlation into an understanding and the results is directly expressed in a piece of paper, with an animation that is easily understood by the maker, was implemented. Therefore, this research is also aimed at finding out whether the implementation of Mind Map technique can increase the studentsâ competence in doing the TOEFL test.This technique was applied on the basis of the single-group-design experiment, where the research was conducted in one group only. Drawn as one group pre-test + post-test: O1Â XÂ O2, this design tries to use the subjects as controls for themselves and omits the control group. This design is also called ârepeated measuresâ design because the subjects are measured two times at its dependent variable. The treatment was conducted 8 times, one pre-test and one post-test. The data was analyzed by using t-test to know the difference between the early and final ability.Based on the data analysis, it can be concluded that Mind Map technique can increase the subjectsâ ability to do the TOEFL test so that their scores can also increase. The results of the analysis shows that the index of tobserved is -11,621 or tabsolute 11,621, higher than the index of ttable at df 30 and significance level of 5%, that is 2,042. Meanwhile, the difficulties the students have include the difficulties in matching the limited test time duration, identifying the pronunciation at listening section, mastering the grammar and vocabulary, as well as understanding the reading text content. The subjects also have positive perception toward the implementation of this technique to increase their ability in doing the test. They consider that Mind Map technique can help them do the test guided, systematically, and enjoyable.